Peningkatan Pemahaman Mahasiswa Jurusan Akuntansi Syariah tentang Penggunaan Pendekatan Etnometodologi - Mohamad Anwar Thalib (Penerbit Goodwood, 2023)
Purpose: The research departs from the problem of the need for more understanding of students majoring in Islamic accounting regarding the use of social theory (ethnomethodology) for the study of cultural accounting. This is reflected, among others, that there are still many students majoring in Sharia accounting who have yet to be able to complete their studies on time. This study aims to increase the understanding of students majoring in Islamic accounting about the ethnomethodology approach, especially the use of this approach in cultural accounting research. Methodology: There are three methods in the implementation of the training. First, the presentation of ethnomethodology, which includes the definition of ethnomethodology, indexicality data analysis techniques, and reflexivity data analysis techniques, and giving examples of the use of ethnomethodology in everyday life. Second, giving examples of cultural accounting research using an ethnomethodology approach that has been published in nationally accredited journals, there are three examples of previous research provided, namely research published in Sinta journals. Third, training on the use of ethnomethodology for accounting research. Results: Corrupt behavior among regional elites still occurs because The training results show an increase in the understanding of students majoring in Islamic accounting about the use of ethnomethodology for cultural accounting research. Furthermore, students have used this approach in cultural accounting research. Conclusion: through this activity, it can be concluded that there is an increase in students' understanding of the use of an ethnomethodological approach to cultural accounting research